Inversion of the Dual Dunkl-Sonine Transform on R Using Dunkl Wavelets - Mourou, M.A. (Symmetry, Integrability and Geometry: Methods and Applications, 2009)
We prove a Calderón reproducing formula for the Dunkl continuous wavelet transform on R. We apply this result to derive new inversion formulas for the dual Dunkl-Sonine integral transform.